Integrated, Marketing Integrated Marketing Communication on Embryo Attractiveness of Marine Tourism Destinations through Brand Building - Wahyu Eko Pujianto; Musyaffaah, Lailatul; Al Haromainy, Muhammad Muharrom; Angga Lisdiyanto (Jurnal Iqtisaduna, 2022)
Sidoarjo district have an embryo maritime tourism destinations that can be a tourist destination for nautical Sidoarjo district. But, the maritime tourism still has not been exposed or promoted with maximum, so that there are many local communities, global and foreign that have not located a maritime tourism and the beauty of tourism destinations that are owned by sidoarjo. So necessary right to marketing and measurable tourist destination program. The purpose of this study is to find and testing whether integrated marketing communication influences attractiviness the embryo tourism destination, Whether integrated marketing communication impact on brand building tourism destination, and do brand building an influence on thr attractiveness of the embryo tourism destination. This research of quantitative research using a Partial Least Square ( PLS ). Population in this research is all visitors tourism in Sidoarjo district. A sample in the research used design probability sampling by choosing 80 visitors maritime tourism in the sample Technique analysis in research that is descriptive and statistic analysis inferential with the methods Partial Least Square (PLS). The research result explain that integrated marketing communication influences attraction, integrated marketing communication influences brand building , and brand building influences attraction.